Cerebrospinal Meningitis caused by micrococcus catarrhalis - Arce, Julián (1921)
Last December, a few days after entering my room "Dos de Mayo" a sick, apparently from sleeping sickness, hospital came another subject, presenting symptoms, at first glance, similar to those we observed in the earlier, resulting in our minds the doubt about the diagnosis, the course of events and the study of market, soon dispelled.